PERILAKU WISATAWAN MUSLIM SEBELUM DAN SELAMA PANDEMI COVID-19 - Nadhira Nazia Allodya Putrisyah, - (2021)
This study aims to analyze differences of the Muslim tourists behavior based on cultural, social, individual, psychological and religiosity factors before and during the COVID-19 pandemic. The research method used is quantitative with a comparative research design. The analysis tool used is SPSS 25 for windows. The subjects of this study were the Muslim millennial generation who had or had never traveled during the COVID-19 pandemic with a total sample of 235 respondents. The results showed that the behavior of Muslim tourists before and after the pandemic was influenced by three dimensions / factors, namely culture, individuals, and psychology. Respondents did not really have a significant difference between before and after the pandemic when viewed based on social factors and religiosity. The results of this study are expected to be useful for tourism development in and can be an input for stakeholders, especially travel agents.